2019
DOI: 10.1016/j.compositesb.2019.107337
|View full text |Cite
|
Sign up to set email alerts
|

Graphene type dependence of carbon nanotubes/graphene nanoplatelets polyurethane hybrid nanocomposites: Micromechanical modeling and mechanical properties

Abstract: Micromechanical modeling and mechanical properties of polyurethane (PU) hybrid nanocomposite foams with multi-walled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs) were investigated by mean of tensile strength, hardness, impact strength and modified Halpin-Tsai equation. Three types of graphene, with varied flake sizes and specific surface areas (SSA), were utilized to study the effect of graphene types on the synergistic effect of MWCNT/GNP hybrid nanofillers. The results indicate a remarkable sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Before the PU synthesis, used MWCNTs were functionalized with hydrogen peroxide (H 2 O 2 ) to better interconnecting GNPs and formation of 3D structure in the polymer matrix, as reported elsewhere. [21,22,30] Different contents and ratios of MWCNTs and graphene were first mixed with polyol at 200 to 2000 rpm for 5 minutes using overhead stirrer equipment. Subsequently, the combination was ultrasonically dispersed for 5 minutes using ultrasonication and stirred again at 2000 rpm about 5 minutes.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the PU synthesis, used MWCNTs were functionalized with hydrogen peroxide (H 2 O 2 ) to better interconnecting GNPs and formation of 3D structure in the polymer matrix, as reported elsewhere. [21,22,30] Different contents and ratios of MWCNTs and graphene were first mixed with polyol at 200 to 2000 rpm for 5 minutes using overhead stirrer equipment. Subsequently, the combination was ultrasonically dispersed for 5 minutes using ultrasonication and stirred again at 2000 rpm about 5 minutes.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…[14][15][16][17][18] Recent experimental results indicate that combining two different nanocarbon fillers with varied sizes as hybrid fillers could lead to a synergistic effect because of a three-dimensional (3D) thermally conductive network formation, which exceeds the thermal properties of the individual graphene or carbon nanotubes filled nanocomposites. [17,[19][20][21][22][23][24][25][26][27] Yu et al [28] achieved a significant thermal conductivity enhancement for graphene and single-walled CNTs hybrid fillers with a weight ratio of 3:1. He et al [20] reported that the thermal conductivity was enhanced with 3D hybrid GNPs/CNTs inclusion in the polymer matrix at very low nanofiller loading.…”
Section: Introductionmentioning
confidence: 99%
“…Although the interfacial bond strength is very critical in determining the tensile/flexural strength [24], the existing models (e.g., Halpin-Tsai model [25] and Kelly-Tyson model [26]) typically assume a homogenous dispersion and perfect bond between CNTs and the hosting matrix [27]. Therefore, few researchers have modified the existing models by adding a multiplier of dispersion coefficient [28][29][30]. The different dispersion mechanisms of CNTs in cement matrix, however, limits the applicability of the existing models to CNT-cement composites.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional models, however, are unable to accurately predict the elastic modulus of nanocomposites in most cases [26,27], because these models disregard CNT dispersion and bonding characteristics within the hosting matrix. To overcome this, few researchers tried to modify the conventional models by including the CNT aggregation-related constants to fit the model to the experimental test data [28][29][30]. However, these modified models are empirical (i.e., without a physical meaning) and underestimate the elastic modulus of CNTreinforced nanocomposites below certain CNT concentrations [28].…”
Section: Introductionmentioning
confidence: 99%